2020
DOI: 10.3126/kumj.v18i1.33367
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Efficacy of Triple Drug Therapy and Sequential Drug Therapy in the Eradication of Helicobacter Pylori with Respect to Antigen Stool test: A Pilot Study

Abstract: Background Helicobacter pylori is one of the most prevalent infectious disease worldwide. The treatment regimens involve mainly two therapies: Standard Triple drug therapy and Sequential drug therapy. Several studies have shown that the sequential therapy has higher eradication rates of H. pylori than the standard triple drug therapy and since proper study on sequential drug therapy and standard triple drug therapy is still lacking in Nepal, this study is attempted to compare efficacy of Sequential Drug Therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…21 However, another prospective study in similar setting by Shrestha et al reported relatively better eradication rate (89%) with sequential therapy. 22 In a recent randomized controlled trial from India, the eradication rate with sequential therapy was found to be 92.9%, which is much higher than the current study. 23 These differences in the eradication rates of sequential therapy can be explained on the basis of different population groups with possibly varying resistance rates to the antibiotics.…”
Section: Discussioncontrasting
confidence: 64%
“…21 However, another prospective study in similar setting by Shrestha et al reported relatively better eradication rate (89%) with sequential therapy. 22 In a recent randomized controlled trial from India, the eradication rate with sequential therapy was found to be 92.9%, which is much higher than the current study. 23 These differences in the eradication rates of sequential therapy can be explained on the basis of different population groups with possibly varying resistance rates to the antibiotics.…”
Section: Discussioncontrasting
confidence: 64%
“…Figures 2 and 3 summarize the risk of bias in the findings of the included studies. Risk of bias summary: review authors' judgements about each risk of bias item (low risk, unclear risk and high risk) for each included study [31,[35][36][37][38][39][40][42][43][44][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][93][94][95][96][97][98][99][100][101][102][103][104].…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…Over half (n = 38) of the included studies were conducted in Asia, over one-third (n = 22) were conducted in Europe and four took place each in South America and Africa (Figure 5). Thirty-eight of the studies [46][47][48][49][50][51][52][54][55][56][57][58][59][60][61][62][63]65,67,68,[71][72][73][81][82][83][84][85][86]93,95,100,104] were performed in Asia (mainly China and Korea but one in Japan, one in Singapore and one in India). Twenty-two were conducted in Europe [31,[35][36][37][38][39][40][41][42][43][44]66,[77][78][79]…”
Section: Geographic Regionmentioning
confidence: 99%